Pengaruh Daya Tarik Wisata Terhadap Kepuasan Wisatawan Pantai Ujung Batu Kota Padang - Idris, Mohammad Azry; Novadilastri; Riesa, Rafidola Mareta (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of tourist attraction on tourist satisfaction at Ujung Batu Beach, Padang City. The method used in this study is a quantitative method with a descriptive approach, and data were collected through questionnaires distributed to 100 respondents. The analysis method used is simple regression analysis. Data testing was conducted using validity and reliability tests, followed by classical assumption tests, namely normality and linearity tests, then hypothesis testing and determination coefficient tests using SPSS 22 as a data processing tool. The results show a positive and significant influence of service quality on visitor satisfaction, with a t-value of 15.804 > t-table 1.661 and a significance value of 0.000 (less than 0.05). The R Square value is 0.718, which means that the influence of the tourist attraction variable (X) on tourist satisfaction is 71.8%, while the remaining 28.2% is influenced by other variables not discussed in this study.